A self-biased fuel cell with TiO2/g-C3N4 anode catalyzed alkaline pollutant degradation with light and without light—What is the degradation mechanism?. (20th August 2016) - Yu, Tingting; Liu, Lifen; Li, Liang; Yang, Fenglin
Graphical abstract: Highlights: The spontaneous e − transfer within TiO2 /g-C3 N4 activates O2 . No voltage applied, inherent potential difference promotes e − transfer. A self-biased electrochemical system generates electricity (∼0.6 V). The anodic RhB removal is ∼98% with a 1000 Ω resistance (without light). The degradation mechanism was discussed with ESR analysis. Abstract: A new self-sustained fuel cell system was established using anodic TiO2 /g-C3 N4 and cathodic Pt nano-catalysts. It is effective for pollutant Rhodamine B (RhB) removal in the alkaline anolyte (0.5 mol L −1 Na2 SO4 + 0.5 mol L −1 NaOH). The cell voltage can reach ∼ 0.6 V (1000 Ω). The anodic RhB degradation was affected by the system circuit connection modes (short-circuit, 1000 Ω and open-circuit). It was themost effective when an external 1000 Ω resistance was connected, and removed ∼98% RhB in the anode chamber (350 mL, 10 mg L −1 RhB). Compared to the traditional method, it does not need any applied voltage or light irradiation to remove RhB. Cyclic voltammetry curves (CV) of TiO2 /g-C3 N4 anode in different electrolytes indicate excellent oxidation capacity at lower potential under alkaline than neutral condition. Presence of RhB under Ultraviolet light (UV) did not increase the system oxidation current as significantly as those without light under alkaline condition. The proposed mechanisms for RhB degradation were caused by the dark activation of O2 and formation of reactive oxidizing species (ROS such as O2 − ). It was confirmed by the electron spin resonance (ESR), even under open-circuit voltage (OCV) condition. The anodic TiO2 /g-C3 N4 catalyzed O2 activation and pollutant oxidation. The RhB removal doesn't decrease as the temperature drops, because of the increase in dissolved oxygen (DO) and the formation of ROS. To cold season, this is a significant advantage compared with microbial methods for practically wastewater treatment.